APPLICATION OF NOBLE GASES AND THEIR ISOTOPES IN THE HYDROGEOLOGY - Kirchheim, Roberto Eduardo; Chang, Kiang Huang [UNESP]; Gastmans, Didier [UNESP]; Ezaki, Sibele; Stradioto, Márcia Regina [UNESP] (Derbyana, 2021)
As the demands for water increase, it is imperative to better assess the dynamics of groundwater circulation in aquifers, information that is considered indispensable for sustainable management. The techniques involving environmental tracers and, among these, specifically those inherent to noble gas isotopes, provide valuable information, such as groundwater residence times and recharge paleotemperatures. Noble gases, namely He, Ne, Ar, Kr and Xe, have physical and chemical properties that vary systematically with their atomic weight, in addition to wide variations in their isotopic compositions resulting from nuclear processes from relatively more abundant parent elements. Because they are inert, noble gases do not undergo chemical and isotopic changes in water-rock interactions. Their presence in groundwater can be interpreted as mixing of atmospheric and non-atmospheric components (radiogenic and/or terrigenous). While the atmospheric component keeps records of past dynamics associated with recharge processes and, therefore, of paleoenvironments and climate, the non-atmospheric components, essentially associated with He isotopes (3He and 4He), as well as radiogenic isotopes, including 81Kr, 85Kr and 39Ar, provide valuable chronological information. This paper presents a complete bibliographic review on the meaning of the concentration of noble gases dissolved in water, their respective components and the methodological paths used to extract hydrogeological information. In the same way, field sampling practices, analytical strategies and methodological paths for data treatment are presented on the basis of the allusion to the main works developed by the international scientific community. Finally, the antecedents of noble gases in Brazil are presented and discussed, with emphasis on the Guarani Aquifer System, which has been the object of pioneering and current development with the application of noble gases. The paper provides a broad view of the use of noble gases and relevant information for the dissemination of these techniques in Brazil.
APLICAÇÃO DE GASES NOBRES E SEUS ISÓTOPOS NA HIDROGEOLOGIA
Keywords: Groundwater; Noble gases; Paleotemperatures; Residence Time